Detecting changes in sediment sources in drought periods: The Latrobe River case study. (November 2016) - Vigiak, Olga; Beverly, Craig; Roberts, Anna; Thayalakumaran, Thabo; Dickson, Michelle; McInnes, Jane; Borselli, Lorenzo
Abstract: The transfer of sediments through the landscape (sediment connectivity) depends on hydrological conditions. This study aimed at assessing changes in sediment sources engendered under extreme drought. A sediment budget model that considered hillslope sediment connectivity was applied to the Latrobe River catchment (South-east Australia) in a relatively normal period (1990–1996) followed by part of the 'Millennium Drought' (1997–2005). Bayesian inference was applied to optimize monthly streamflow and calibrate sediment parameters against mean annual specific sediment yields at ten monitoring stations. In 1990–1996, assessed sediment yield at the outlet was 68 kt/y; 60% of sediments originated from net hillslope erosion and 40% from streambank erosion. In 1997–2005, sediment yield decreased to 13 kt/y, 27% from net hillslope erosion against 65% from streambank erosion. During the drought, both hillslope gross erosion and hillslope sediment connectivity decreased dramatically. Streambank protection is of the utmost importance under all hydrologic conditions and especially during drought periods. Highlights: We explored shifts on sediment connectivity during drought with a conceptual model. Bayesian inference was used for independent calibration of two hydrological periods. Model results indicated that net hillslope erosion declined during drought. During the Millennium Drought, streambank erosion was the major sediment source. Streambank protection is of the utmost importance especially in drought periods.